Communicative Daily Life Stories: Raising Awareness About the Link Between Desire and Violence - Cisneros, Rosa María (Qualitative inquiry, 2021)
Gender violence poses a serious risk for women, girls, and children worldwide. Despite all efforts put forth to curtail it, few successful results have emerged. Narratives have been used to denounce the reality lived by survivors. However, scarcely any literature has explored how they get to question their own reality and, if they do, how these survivors are able to break the circle of gender violence by making room for nonviolent and egalitarian relationships. This article is a step in this direction: It explores how some girls, after participating in an initiative based on the language of desire, known as "Dialogic Feminist Gatherings," encourage one another to question the dominant model of socialization in relationships in which attraction is linked to violent behaviors. The analysis focuses on communicative daily life stories (hereafter CDLS) performed in a Spanish high school with female teens after their participation in the gatherings. Drawing from these stories, the article illustrates how this methodological tool allows one to assess the impact of these gatherings on identifying the existence of this dominant model while also pushing to question it. This article also contributes to a better understanding of the relationship between attraction and violence, a risk factor for gender violence previously noted in the scientific literature. The knowledge obtained through this inquiry reinforces an evidence-based approach to having an effective social impact on the struggle against gender violence